New Management Strategies of Hormone Refractory Prostate Cancer (HRPC) - Salam, MA (Journal of Bangladesh College of Physicians and Surgeons, 2010)
DOI: 10.3329/jbcps.v26i2.4180 J Bangladesh Coll Phys Surg 2008; 26: 58-61